Allyl isothiocyanate actions on populations of Sitophilus zeamais resistant to phosphine: Toxicity, emergence inhibition and repellency. (October 2016) - Freitas, Rita Cristina P.; Faroni, Lêda Rita D'Antonino; Haddi, Khalid; Viteri Jumbo, Luis O.; Oliveira, Eugênio E.
Abstract: The risks associated with the use of synthetic insecticides have caused increased interest in the research of essential oils and their main constituents for use in the pest management of stored products. Allyl isothiocyanate (AITC) is the main component of mustard essential oil and has been reported as a potential replacement pesticide for conventional insecticides that control stored product insect pests. Here, we assessed the toxicity (including emergence inhibition) and repellent actions of AITC on Brazilian populations of the maize weevil Sitophilus zeamais (Coleoptera: Curculionidae) resistant to conventional insecticides (e.g., phosphine). We also evaluated physiological (e.g., respiration) and behavioral (e.g., walking and flight) traits of AITC-exposed insects. The AITC showed consistent insecticidal activity against the populations resistant to phosphine and other synthetic insecticides, with LC50 values ranging from 1.5 to 2.9 μL L −1 . Significant inhibition of the offspring emergence was achieved after the exposure of parental adults to sublethal levels (i.e., LC1 and LC5 ) of AITC. Reductions in respiration rates were also registered in all the populations sublethally exposed to AITC. In all five populations, a high number of insects avoided AITC-treated (1.5 μL L −1 ) grain masses, and although individuals of a phosphine-susceptible (i.e., Abre Campo) population increased walking and reduced flight activities, individuals of another phosphine-susceptible (i.e., Tunápolis) population exhibited higher flight activity under AITC exposure. Thus, our findings suggest that AITC is a potential tool that may be integrated into the control strategies of maize weevils where resistance to phosphine and other conventional insecticides is a problem. Highlights: Allyl isothiocyanate (AITC) controlled phosphine-resistant S. zeamais populations. Parental sublethal exposure to AITC significantly inhibited offspring emergence. Reduced respiration rates were registered in all populations AITC-sublethally exposed. Phosphine-resistant S. zeamais populations avoided AITC-treated grains masses.